Seed addition via epizoochorous dispersal in restoration: an experimental approach mimicking the colonization of bare soil patches. Issue 1 (24th June 2013) - Freund, Linda; Eichberg, Carsten; Retta, Iris; Schwabe, Angelika; Middleton, Beth
Abstract Questions Does epizoochorous dispersal via sheep lead to the establishment of populations of sandy grassland species on newly created, managed restoration sites on sandy bare soil? Do epizoochorously‐induced spatial patterns persist during vegetation development? Does sandy grassland develop, which is rich in epizoochorously‐dispersed target species? Location Upper Rhine Valley, Germany. Methods A 6‐yr experiment on epizoochorous dispersal by sheep was conducted on three newly created deep sand deposition sites mimicking restoration areas with reduced nutrient availability. Establishment success and persistence of ten epizoochorously‐dispersed species were assessed and spatial patterns were analysed using SADIE (Spatial Analysis by Distance Indices). Vegetation development of the experimental areas was related to a nearby nature reserve (relevés, target species ratios). In addition, seed rain and early‐successional soil seed bank were sampled. Results All but one species dispersed by sheep became established and persisted during the 6‐yr study. After establishment, most perennials did not change or increased in abundance over time, whereas annuals showed various population dynamics. Spatial patterns were aggregated for most study species. Similarity of spatial patterns between consecutive years varied by species, site and year, and was stronger in perennial than in annual species. Patterns of seed dispersal and establishment were positively associated with each other (a subset of three species was tested). Within 6 yrs, the proportion, but not the cover, of target species in the experimental areas reached a level similar to that of a nearby nature reserve; however, many species characteristic of the nature reserve were absent. The species compositions of both seed bank and seed rain were dominated by non‐target species. Conclusions Sheep flocks may assist in colonization of grassland species on newly created bare soil areas via epizoochory. The incorporation of livestock into restoration projects might facilitate the regeneration and preservation of threatened plant populations. Livestock might be most successful in promoting biodiversity if they are moved from communities with target species to restoration areas.